Switching consumers and product liability: on the optimality of incomplete strict liability - Florian Baumann; Tim Friehe; Kristoffel Grechenig (Max Planck Institute for Research on Collective Goods, 2010)
This article shows that it may be socially optimal to grant accident victims less than full compensation. In our framework, firms are liable under product liability but also invest in care to prevent consumers switching to competitors. Affecting the partition of consumers by means of care-taking is not desirable from a social standpoint. Consequently, it may be optimal to reduce liability below full compensation in order to adjust firms' care incentives.
Keywords: K13; 330; Tort law; product liability; care level; asymmetric information; switching